1998
DOI: 10.1302/0301-620x.80b3.0800432
|View full text |Cite
|
Sign up to set email alerts
|

The influence of osteoporosis on varus osteoarthritis of the knee

Abstract: W e studied 37 patients with varus osteoarthritis of the knee to determine the influence of the bone mineral density (BMD) on the varus deformity. There were 15 men (21 knees) and 22 women (38 knees). The mean age of the men was 69 years and of the women 68 years. BMD was measured in the L1-L4 spinal region using dual X-ray absorptiometry. In the women a low level of BMD was associated with varus deformity originating at the proximal tibia, but a high level was predominantly linked with deformity originating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Some patients with low bone mass could, therefore, be classified as having radiological grade 4 rather than grade 3. These suggestions are consistent with evidence reported by Terauchi et al 23 that there are two types of varus OA of the knee: one caused by low bone mass, and the other associated with high bone mass. In the present study, because the mean BMD in grade 4 in the OA group was higher than that in the control group, it is possible that the number of patients with radiological grade 4 with high BMD may be much greater than the number with low BMD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Some patients with low bone mass could, therefore, be classified as having radiological grade 4 rather than grade 3. These suggestions are consistent with evidence reported by Terauchi et al 23 that there are two types of varus OA of the knee: one caused by low bone mass, and the other associated with high bone mass. In the present study, because the mean BMD in grade 4 in the OA group was higher than that in the control group, it is possible that the number of patients with radiological grade 4 with high BMD may be much greater than the number with low BMD.…”
Section: Discussionsupporting
confidence: 93%
“…1,17,21 Recently, however, Terauchi et al 23 have reported varus OA of the knee caused by low bone mass, in which the varus deformity originated from trabecular microfractures in the proximal tibia and, consequently, increased stress on the articular cartilage. Furthermore, the Baltimore study of aging showed that although men, but not women, with definite knee OA had significantly greater radial bone mass and size, subjects with knee OA did not have significantly higher bone mineral density (BMD) in the upper extremity.…”
mentioning
confidence: 99%
“…These findings suggest that the participants likely had mild to moderate disease severity. It is important to note, though, that medial joint space narrowing does not always result in varus alignment but rather a change in the angle between the femoral condyles and the femoral shaft and/or between the tibial plateau and tibial shaft (44). Some limitations of this study must be considered.…”
mentioning
confidence: 90%
“…This finding is supported by the finding that during walking, approximately 70% of total load is typically transmitted through the medial compartment in the normal knee joint (Hurwitz et al 1998). Degenerative joint disease, osteoarthrosis (OA) when severe, leads to relative sclerosis beneath the loaded condyle and relative porosis beneath the unloaded condyle, with the strongest bone being found on the concave side of the deformity (Terauchi et al 1998). In previous studies, the tibial BMD of the medial compartment has been shown to be significantly higher than that of the lateral compartment, both in mild and severe OA (Akamatsu et al 1997, Wada et al 2001.…”
mentioning
confidence: 92%